Advances in nucleic acid probe-based detection of gene point mutations: a review - Pu, Xuyang; Wu, Xueqiang (Frontiers in Chemistry, 2025)
A fundamental characteristic of gene mutations is the permanent alteration of the DNA sequence, including point mutations, deletions, inversions, and translocations. Among these, DNA point mutation detection has consistently remained a central focus of research across multiple disciplines due to its close association with a range of diseases, such as sickle cell anemia and β-thalassemia. However, the typically low abundance of such mutations presents a significant technical challenge. Due to technical limitations in detection sensitivity, increasing research efforts have been directed toward nucleic acid probe-based strategies to enhance the efficiency and accuracy of point mutation identification. This review summarizes the developments in nucleic acid probe-based techniques for detecting gene point mutations, with an emphasis on strategies involving pure nucleic acid probes as well as the synergistic use of enzymes, nucleic acid analogs, and nanotechnology. The principles, advantages, and limitations of the above technologies are also described and summarized. In addition, we also explored the application of AI technology in nucleic acid probes and the potential future challenges.